PENGARUH CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITY, TAX PLANNING, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERATING - Dina Pujianti; Alfiati Silfi; Eka Hariyani (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2023)
This study aims to examine the effect of corporate social responsibility, profitability, tax planning, and capital structure on firm value with managerial ownership as a moderating variable in manufacturing companies listed on the Indonesian Stock Exchange. This research is a quantitative research that uses secondary data. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2018-2020 period. The research sample was selected using purposive sampling method, so that the samples obtained were 53 samples. The data was obtained through the official website of the Indonesian Stock Exchange and other related websites as well as by studying literature related to research issues, both printed and electronic media software (Statistical Package for Social Science) The results show that the independent variables, namely CSR, profitability, tax planning, and capital structure affect the dependent variable, namely firm value. The moderating variable, namely managerial ownership, is known to be able to moderate the effect of CSR, profitability, tax planning, and capital structure on firm value.